Optimization Design of Insert Hot Stamping Die’s Cooling System and Research on the Microstructural Uniformity Control of Martensitic Phase Transitions in Synchronous Quenching Process - Xin Shang; Lijuan Pang (Advances in Materials Science and Engineering)
Ultrahigh-strength steel BR1500HS was chosen as the research object. The parameters of insert hot stamping die’s cooling system in the synchronous quenching process were calculated, and the cooling system was designed based on the temperature distribution of formed part. Then, by combining FEM simulation and thermal-mechanical coupling theory of synchronous quenching process of hot stamping, the cooling system was optimized. After that, the punch and die were optimally designed based on the simulation of temperature field of formed part as well as dies, and their temperature decreased by 15°C and 12°C, respectively. Next, the microstructural evolution in austenization and synchronous quenching processes was analyzed. By adopting a synchronous cooling system in hot stamping, by optimizing the parameters and control strategies, and by controlling the water velocity in various inserts, the homogeneity of martensitic phase transitions was improved. The results of the application test show that martensitic phase transitions of major parts are uniform under given working conditions, and hardness difference of each part was small.